Lecture VII: Mantra, and questions and answers - Stockhausen, Karlheinz 1928-2007 (Kürten Stockhausen Verlag, 2007)
Lecture VII:MANTRA and Questions and Answers on MANTRA given on July 19th 1973 at the ImperialCollege in London.